Transformation of Two Cases of Lung Adenocarcinoma into Pulmonary Sarcomatoid Carcinoma following Treatment - Zhenyu Yang; Yinfang Shen; Junhong Jiang; Ziyi Liu; Chuanyong Mu (Canadian Respiratory Journal)
Accumulating evidence shows that histologic transformation is involved in the drug resistance of lung cancer. Moreover, it is common for lung adenocarcinoma to transform into small-cell lung cancer or squamous cell carcinoma; however, clinical cases with sarcomatoid transformation have been rarely reported. Thus, both the diagnosis and treatment of lung adenocarcinoma with sarcomatoid transformation remain difficult. Here, we discuss two patients with lung adenocarcinoma with sarcomatoid transformation—analyzing the diagnosis, clinical features, immunohistochemical characteristics, therapy, and prognosis—with the hope that this report will be used as a reference for future treatment of these patients.